Value Of Tolerance In Gina Prince's The Secret Life Of Bees Movie (2008): A Marxist Approach - Cahyaningsih, Yeni (2012)
The problem of the study is to reveal value of tolerance reflected in The Secret Life of Bees movie directed by Gina Prince Bythewood published in 2008. The objectives of the study are to analyze the film based on structural analysis and based on the Marxist analysis. This study is descriptive qualitative study. The object of the study is The Secret Life of Bees movie directed by Gina Prince Bythewood. The data sources are divided into two namely primary and secondary data source. The primary data source is the film itself and the secondary data source is the other source related to the analysis such as references, author biography, criticisms relation to the problem and material related to the study whether picking up from books or internet. The methods of data collection are observation and library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, based on the structural analysis, Gina Prince delivers a message that the blacks have a high tolerance in the discrimination. Tolerance is important in the society, as black and white. They must be have tolerance. The black just wants a little respect from the whites as a human being. Racial discrimination can be changed with tolerance because the blacks have rights to live in the world. Second, based on Marxist analysis, Gina Prince reflects the racial discrimination by present Marxist issues in this movie. The blacks can be survived with the race prejudice which comes from the whites.